Presence and absence of the Spanish women's magazines in social networks. Analysis of their interactivity on Facebook, Twitter and Instagram - Ganzabal Learreta, María (2022)
The digitalization of the women's magazines has brought with it the use of a multitude of Web 2.0 resources. The latest to appear are the social actors that, since 2006, have become the new spaces for the women's press to meet with readers. In this study we wanted to analyze, through content analysis, how the five main Spanish women's magazines Vogue, Elle, Telva, Woman and Marie Claire behave in the three social networks that are common to all of them: Facebook, Twitter and Instagram. Although each social network has its own specificities, we did not find any real communities of readers or two-way interactivity on the part of the publications.  Nor have we noticed their presence in new social networks such as Tik Tok or Twitch where there is a younger audience and with which they should get involved as soon as possible